Mobile Satellite Communications Handbook - Cochetti, Roger (Hoboken : Wiley, 2014)
Mobile Satellite Communications Handbook, Second Edition, serves to provide background for the earliest proposals to the most current advances in technology used for INMARSAT and NON-INMARSAT mobile-satellite communications. Revised edition will serve both technical and non-technical professionals who rely every day on mobile satellite communications Describes and explains historic, current, and planned civil, commercial, and military mobile satellite communication systems. 1st Edition charts and tables updated and expanded with current material for today's mobile satellite technology.
Appendix IV: Mobile Satellite Communications Excerpts From U.S. Federal Communications Commission Report on U.S. Commercial Mobile ServicesIndex; End User License Agreement.
Print version record.
Keywords: Artificial satellites in telecommunication; Mobile communication systems; Artificial satellites -- Electronic equipment -- Handbooks, manuals, etc; Artificial satellites in telecommunication -- Handbooks, manuals, etc; Mobile communication systems -- Handbooks, manuals, etc; Artificial satellites in telecommunication; Mobile communication systems; Electronic books